2002
DOI: 10.1021/ja012555f
|View full text |Cite
|
Sign up to set email alerts
|

The First Example of a Nitrile Hydratase Model Complex that Reversibly Binds Nitriles

Abstract: Nitrile hydratase (NHase) is an iron-containing metalloenzyme that converts nitriles to amides. The mechanism by which this biochemical reaction occurs is unknown. One mechanism that has been proposed involves nucleophilic attack of an Fe-bound nitrile by water (or hydroxide). Reported herein is a five-coordinate model compound ([Fe III (S 2 Me2 N 3 (Et,Pr))] + ) containing Fe(III) in an environment resembling that of NHase, which reversibly binds a variety of nitriles, alcohols, amines, and thiocyanate. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
116
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(123 citation statements)
references
References 53 publications
7
116
0
Order By: Relevance
“…[14][15][16][17][18] A significant number of structurally relevant model complexes have been reported, some of which bind nitriles and some of which reversibly bind NO and show photolytic behavior. [19][20][21][22] Furthermore, the study of a series of model complexes having oxidized ligands has shown that this oxidation can significantly alter the pK a of a water bound to the low-spin Fe III . 23 Ligand K-edge X-ray absorption spectroscopy (XAS) is a direct probe of a ligand's chemical nature and its bonding to a metal.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] A significant number of structurally relevant model complexes have been reported, some of which bind nitriles and some of which reversibly bind NO and show photolytic behavior. [19][20][21][22] Furthermore, the study of a series of model complexes having oxidized ligands has shown that this oxidation can significantly alter the pK a of a water bound to the low-spin Fe III . 23 Ligand K-edge X-ray absorption spectroscopy (XAS) is a direct probe of a ligand's chemical nature and its bonding to a metal.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc, [1][2][3][4][5][6][7] nickel, [8][9][10][11][12] and iron [13][14][15][16][17][18][19][20] thiolate complexes have been made as models for mononuclear and polynuclear metalloenzyme active sites with RSÀM coordination. The alkylthiolate functionality is important because of its relevance to cysteinate ligation, but it is also quite challenging to control from a synthetic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…2, the acetate is coordinated in a monodentate, as opposed to bidentate, fashion trans to an imine nitrogen [N(1), Table 1]. As is the case with structures 3 and 5, the FeOS bond in 6 (Table 1) falls on the short end of reported low-spin Fe(III) thiolate structures (21,22,30). Again, this most likely reflects the cationic molecular charge and the weaker trans influence of the amine nitrogen [N(2)] relative to anionic ligands such as N 3 Ϫ or SCN Ϫ .…”
mentioning
confidence: 99%
“…4b) are roughly half [as opposed to significantly less (23,30)] as intense as the oscillations due to first coordination sphere atoms (rЈ between 1 and 2 Å). Because scattering by C is not significantly different from that by N, we initially analyzed the first sphere (rЈ ϭ 0.8-2.0 Å) Fourier filtered (FF 1 ) EXAFS by using a single S scatterer and five N scatterers; the latter were distributed among one or more shells, each with an integral n (no.…”
mentioning
confidence: 99%
See 1 more Smart Citation